Institutional Aspects of Economic Systems Management - OSTANINA, Sofia Sh.; AVILOVA, Vilora V.; ALEKSANDROV, Andrey Y.; MAKHOTKINA, Liliia Y.; PUGACHEVA, Anna S. (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
The relevance of the study is conditioned by the development of institutional innovations of economic systems’ management. Selecting of alternative institutional innovations is associated with the probability of suboptimal institutions’ introduction that blocks more effective options for economic development. The purpose of the paper is to identify the institutional aspects of management of economic systems. The leading approach is the institutional one that allows considering of the institutional aspects of economic systems’ management as a source of their development and preconditions of activities’ organization focused on costs’ reducing connected with excessive government regulation of the economy, and the formation of effective tools for interaction of federal executive bodies in the implementation of functions. The paper presents the essential characteristics of the institutional order, the institutional environment and institutional structure and establishes their relationship; presents the institutions’ Russian experience of state orders’ placement and the organization of the institutional environment; reveals the significances of communitarian values in the development of economic systems; offers the development of institutional structure of the service sector; clarifies the characteristics of the institutional aspects of economic systems’ management (multi-levelness, duality, fragmentariness). The paper submissions may be useful for specialists of federal and regional authorities, local authorities, ministries and scientists interested in the regional economy and institutional innovations in the management of economic systems.